2021
DOI: 10.1186/s12879-020-05639-7
|View full text |Cite
|
Sign up to set email alerts
|

Variation in Mycobacterium tuberculosis population structure in Iran: a systemic review and meta-analysis

Abstract: Background Acquiring comprehensive insight into the dynamics of Mycobacterium tuberculosis (Mtb) population structure is an essential step to adopt effective tuberculosis (TB) control strategies and improve therapeutic methods and vaccines. Accordingly, we performed this systematic review and meta-analysis to determine the overall prevalence of Mtb genotypes/ sublineages in Iran. Methods We carried out a comprehensive literature search using the in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 47 publications
(28 reference statements)
1
6
0
Order By: Relevance
“…The MIRU-VNTR and spoligotyping methods have proven capacities to correctly identify and discriminate between MTBC lineages. Our ten-year studies confirm the absence of the M. tuberculosis genotypes L3/CAS and L1/EAI sublineages in Bulgaria, which are widespread in Northern India, Pakistan, Afghanistan, Iran, and Iraq [12,47,62,63,[67][68][69]. Northwest India is the presumed geographical area of the Gypsy communities that migrated to Europe 10 centuries ago, crossing Pakistan, Afghanistan, Iran, Iraq, and Turkey (Figure 3).…”
Section: Discussionsupporting
confidence: 74%
See 1 more Smart Citation
“…The MIRU-VNTR and spoligotyping methods have proven capacities to correctly identify and discriminate between MTBC lineages. Our ten-year studies confirm the absence of the M. tuberculosis genotypes L3/CAS and L1/EAI sublineages in Bulgaria, which are widespread in Northern India, Pakistan, Afghanistan, Iran, and Iraq [12,47,62,63,[67][68][69]. Northwest India is the presumed geographical area of the Gypsy communities that migrated to Europe 10 centuries ago, crossing Pakistan, Afghanistan, Iran, Iraq, and Turkey (Figure 3).…”
Section: Discussionsupporting
confidence: 74%
“…The L4.2.2.1/TUR sublineage is geographically restricted to the Balkan Peninsula (Albania, Bulgaria, Serbia, and Turkey) and Syria, both of which were part of the Ottoman Empire from the 14th century to the 19th century [1,60,61]. The prevalence in other countries where ethnic groups of Turkic origin live, i.e., Iran (Azeri) or China (Uygurs), is less than 1% [62][63][64]. In Bulgaria, during 2008-2018 the prevalence of the L2/Beijing genotype was low (18/1041; 1.7%).…”
Section: Resultsmentioning
confidence: 99%
“…14 However, the finding of this study is higher than in studies conducted in South Africa (52.2%); Addis Ababa (27.3%), West Gojjam Zone (23%), and Bahir Dar City administration (35.6%), Ethiopia; Free State Province, South Africa (38.8%); and Moyen-Ogooue Province, Gabon (54.4%); and a study conducted in China found that N95 respirators were not available for HCWs and surgical masks were not available for TB patients and suspects. 7–9 , 13 , 20 , 26 , 27 The different results could be attributed to supply differences, study period, the current study being conducted during the coronavirus disease 2019 (COVID-19) pandemic, study setting, and type of health care facilities.…”
Section: Discussionmentioning
confidence: 95%
“…The Delhi/CAS prevalence varies in different parts of Iran, although it seems to be more common in the central provinces. A systematic review study considered this sub-lineage the second most prevalent (19.2%) circulating genotype in Iran (Hadifar et al 2021 ). As Khuzestan province is adjacent to Iraq, the study conducted by Ahmed et al ( 2014 ) can reasonably compare our findings.…”
Section: Discussionmentioning
confidence: 99%
“…Since then, researchers from various regions, especially in the north and the capital, have repeatedly reported it (Kochkaksaraei et al 2019 ; Azimi et al 2018 ). The NEW-1 sub-lineage was identified as the dominant (21.9%) circulating genotype in Iran by a systematic review of studies of the last decade (Hadifar et al 2021 ). In a multicenter study covering nine Iranian provinces, the NEW-1 sub-lineage made up the most (41.2%) resistant isolates (Mousavi et al 2020 ).…”
Section: Discussionmentioning
confidence: 99%